Effects of two neuromuscular training programs on running biomechanics with load carriage: a study protocol for a randomised controlled trial - Liew, Bernard X. W. (BMC Musculoskelet Disord, 2016)
BACKGROUND: In recent years, athletes have ventured into ultra-endurance and adventure racing events, which tests their ability to race, navigate, and survive. These events often require race participants to carry some form of load, to bear equipment for navigation and survival purposes. Previous studies have reported specific alterations in biomechanics when running with load which potentially influence running performance and injury risk. We hypothesize that a biomechanically informed neuromuscular training program would optimize running mechanics during load carriage to a greater extent than a generic strength training program. METHODS: This will be a two group, parallel randomized controlled trial design, with single assessor blinding. Thirty healthy runners will be recruited to participate in a six weeks neuromuscular training program. Participants will be randomized into either a generic training group, or a biomechanically informed training group. Primary outcomes include self-determined running velocity with a 20 % body weight load, jump power, hopping leg stiffness, knee extensor and triceps-surae strength. Secondary outcomes include running kinetics and kinematics. Assessments will occur at baseline and post-training. DISCUSSION: To our knowledge, no training programs are available that specifically targets a runner’s ability to carry load while running. This will provide sport scientists and coaches with a foundation to base their exercise prescription on. TRIAL REGISTRATION: ANZCTR (ACTRN12616000023459) (14 Jan 2016) ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12891-016-1271-9) contains supplementary material, which is available to authorized users.